Omalizumab for STAT3 Hyper-IgE Syndromes in Adulthood: A Case Report and Literature Review - Lan, Jun; Zhang, Yi; Song, Min; Cai, Shan; Luo, Hong; OuYang, Ruoyun; Yang, Pan; Shi, Xiaoliu; Long, Yingjiao; Chen, Yan (Frontiers in Medicine, 2022)
Background Hyper-immunoglobulin E (IgE) syndromes (HIES) are a group of primary immune deficiencies disorders (PID) characterized by elevated serum IgE, eczema, recurrent skin, or respiratory system infections and may also be accompanied by some connective tissues and skeletal abnormalities. Currently, there is no complete cure or targeted treatment for HIES. Omalizumab is a humanized recombinant monoclonal antibody against IgE, reducing the level of free IgE, inhibiting the binding of IgE to receptors on the surface of effector cells, and reducing the activation of inflammatory cells and the release of multiple inflammatory mediators. However, the effect of omalizumab in treating HIES remains unknown. Herein, we described a case of an AD-HIES patient with chronic airway disease who benefited from omalizumab treatment. Case Presentation A 28-year-old Chinese woman was admitted for recurrent cough for 7 years, markedly elevated serum IgE level, and recurrent pneumonia caused by multiple pathogens, such as Pneumocystis jirovecii, Cytomegalovirus, Staphylococcus aureus, Aspergillus, and Mycobacterium tuberculosis. She had eczema-dermatitis, skin abscess, slightly traumatic fracture since childhood, and developed asthma and allergic bronchopulmonary aspergillosis (ABPA) lately. Using whole-exome sequencing, the STAT3 (c.1294G>T, p.Val432Leu) missense mutation for the autosomal dominant hyper-IgE syndrome was identified, and omalizumab was prescribed at 300 mg every 2 weeks. The patient responded well with the improvement of respiratory symptoms and lung function tests. The level of serum IgE remained stable on follow-up. Conclusion Omalizumab treatment proved beneficial in the case of HIES, especially with chronic airway disease, for which therapeutic options are limited. However, larger-scale prospective studies and long-term follow-up are required to establish the efficacy and safety of this therapeutic intervention.